FORMULASI DAN UJI STABILITAS GEL MASK FRAKSI ETIL ASETAT BUNGA TELANG (Clitoria ternatea L.) SEBAGAI ANTIOKSIDAN - Puspitasari, Dewi Fitriani; Utami, Rani Nur Ayu; Wildan, Achmad (Jurnal Insan Farmasi Indonesia, 2025)
The ethyl acetate fraction of butterfly pea flower was found to have higher antioxidant activity than other fractions. This fraction can be utilized in making gel mask preparations, as an alternative to topical antioxidants. The purpose of this study was to formulate the ethyl acetate fraction in a gel mask preparation, and test the physical characteristics and stability of antioxidant activity before and after being stored for 3 months at room temperature. Extraction of telang flowers, using 70% ethanol, followed by fractionation with n-hexane, ethyl acetate and water. The results of the ethyl acetate fraction were tested for antioxidant activity, then formulated in a gel mask preparation. Evaluation of the physical characteristics of the preparation includes organoleptic test, homogeneity, pH, viscosity, adhesion, spreadability, and antioxidant activity test, before and after 3 months storage with DPPH. The results of the antioxidant activity test of the ethyl acetate fraction obtained a value of 25.14 µg/mL. The results of the physical characteristics of the gel have a pH 5.18 ± 0.035, viscosity 9541 ± 32.14 cps, adhesion 2.04 ± 0.015 seconds, spreadability 4.55 ± 0.015 cm. The antioxidant activity of the gel decreased after storage for 3 months.